How does the intermediaries' power affect farmers-intermediaries' trading relationship performance?. (June 2018) - Xhoxhi, Orjon; Pedersen, Søren Marcus; Lind, Kim Martin
Highlights: Intermediaries' power over farmers' margin reduces relationship performance. Intermediaries' power over harvesting and delivery activities improves performance. Intermediaries' exercise of power impacts relationship development. Policies should change trading parties' mindset from "power over" to "power with". Abstract: The paper investigates the effects of intermediaries' exercise of their power over farmers on the trading relationship performance between them. The trading relationship performance between farmers and intermediaries is conceptualised as being composed of four dimensions, namely (1) Relationship profitability, (2) Relationship flexibility, (3) Product quality and (4) Post-harvest losses. Structural Equation Modelling (SEM) is employed to test the hypotheses of the paper. The SEM analysis shows that intermediaries' power over farmers affects the performance of the relationship in different ways, depending on the dimension of power that they exercise. Thus, when intermediaries' exercise their power over farmers' margin, relationship performance is hampered. On the other hand, when they exercise their power over farmers' input selection activities or over harvesting and delivery activities the performance is improved. Furthermore, the result show that intermediaries' power affects relationship performance also indirectly through relationship quality and conflict between farmers and intermediaries. The mediated effects through relationship quality and conflict of power on relationship performance are in the same line as the direct effects of each dimension of intermediaries' power. The policy implication of these results is that any initiative that aims at enhancing food value chains performance (like reducing post-harvest losses) or improving smallholders business opportunities, should start first by changing the mind-set of the trading parties (especially of intermediaries) "from power over" one another to "power with" each other.